2015
DOI: 10.9738/intsurg-d-14-00167.1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Endoscopy for Diagnosis of Barrett in a Non-Western Society: Endoscopic and Histopathologic Correlation

Abstract: Barrett esophagus is metaplastic transformation of esophageal squamous epithelium to columnar cells. A total of 1370 patients who had undergone upper endoscopy because of dyspeptic complaints were enrolled in the study. Age, sex, alcohol and smoking habits, body mass index, type and duration of symptoms (heartburn, epigastric pain, nausea, vomiting), and use of proton pump inhibitors were evaluated in all patients and recorded on standardized forms. Patients were grouped as normal esophagogastric junction, lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…There were 44 articles that fulfilled the eligibility criteria, [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49 Figure 2). The lowest prevalence was 0.6% reported by two studies, both of which were conducted in Turkey, [41,58] and the highest prevalence was 29%, reported in a study from the US. [17] The pooled prevalence of histologically confirmed BO in individual countries is provided in Figure 2, and the pooled prevalence according to geographical study location is provided in Table 1.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…There were 44 articles that fulfilled the eligibility criteria, [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49 Figure 2). The lowest prevalence was 0.6% reported by two studies, both of which were conducted in Turkey, [41,58] and the highest prevalence was 29%, reported in a study from the US. [17] The pooled prevalence of histologically confirmed BO in individual countries is provided in Figure 2, and the pooled prevalence according to geographical study location is provided in Table 1.…”
Section: Resultsmentioning
confidence: 95%
“…, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59] of which two reported the prevalence of endoscopically suspected BO only,[44,54] 30 reported the prevalence of histologically confirmed BO only,[16,17,18,20,22,23,24,25,26,27,28,29,30,31,32,34,35,37,38,39,42,43,46,47,48,49,51,52,56,58] and 14 included studies[16,19,21,33,36,41,44,45,50,53,54,55,57,59] that reported the prevalence of endoscopic BO among subjects undergoing endoscopic examination for gastro-oesophageal reflux symptoms of any frequency contained 8,817 subjects and were geographically diverse, with three studies from Europe, two from North America, four from the Middle east...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). There were 19 articles that fulfilled the eligibility criteria, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] of which two reported the prevalence of endoscopically suspected BE only, 27,33 13 reported the prevalence of histologically confirmed BE only, [18][19][20][21][22]24,25,[29][30][31][32]34,36 and four reported the prevalence of BE according to both definitions. 23,26,28,35 Agreement between investigators for assessment of study eligibility was excellent (kappa statistic = 0.92).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][28][29][30][31][32][34][35][36] Seven studies were conducted in Asia, 20,22,24,[30][31][32]36 four in Europe, 18,23,26,28 three in North America, 19,25,35 and three from the Middle East. 21,29,34 When data from all 17 studies were pooled, the prevalence of histologically confirmed BE in all individuals was 3.2% (95% CI 1.9% to 4.6%). Among subjects with GER symptoms the prevalence of histologically confirmed BE was 4.3% (95% CI 2.4% to 6.7%), compared with 2.4% (95% CI 1.4% to 3.7%) among those without.…”
Section: Association Between Gastro-esophageal Reflux Symptoms or Gas...mentioning
confidence: 99%